Desestructuración económica y crisis social. El Pacífico Sur costarricense en el marco de la década perdida - Hernández Rodríguez, Carlos (2005)
Through the use of a wide diversity of sources (oral, newspaper, and documentary), this article explores the problem areas of the economic destructuring suffered by the Costa Rican Southern Pacific region, the different social impacts generated by this crisis, the great strike of 1984, and the policies and solutions proposed by the State and other social actors, in the face of these major issues.